Martín Fierro at University of Texas: between the pan-american crusades and the persistence of the gaucho’s libertarian role (1958-1968) - Casas, Matías Emiliano (2021)
This article analyzes one of the most remarkable derivations of the poem Martín Fierro: its use for either Pan-American or anti-Communist purposes. The exploration of the personal archive of one of the main promoters of the gaucho figure in the United States, Dr. Edward Larocque Tinker, together with the “martinfierrista” library of the University of Texas at Austin, sheds light on the variety of meanings attributed in the United States to this Pampean character. At the same time, the persistence of the rebellious and unruly nature of the gaucho is examined in texts published during the Cold War, bringing to the fore unresolved tensions.